2023
DOI: 10.3389/ijph.2023.1604647
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to 24-h Movement Guidelines and Depressive Status During the Coronavirus Disease Outbreak: A Cross-Sectional Japanese Survey

Abstract: Objectives: The coronavirus disease 2019 (COVID-19) pandemic has affected people’s physical activity, sedentary behavior, and sleep. This study aimed to clarify the association between combining these factors, integrated as adherence to 24-h movement guidelines, and depressive status during the COVID-19 pandemic.Methods: At the end of October 2020, we sent self-administered questionnaires to 1,711 adults aged ≥18. We assessed physical activity, sedentary behavior, sleep duration, adherence to 24-h movement gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Meeting 24-HMB guidelines with both categorical (SL + ST and PA + ST + SL)and continuous metrics were beneficially linked to reduced depression and anxiety of those prescribed eyeglasses/contact lenses. Such findings are supported by previous studies on different age groups (e.g., preschoolers, youths, and college students, workers) ( Kitano et al., 2020 ; Ohta et al., 2023 ; Sampasa-Kanyinga et al., 2021 ; Zhu et al., 2023 ) with different health status (e.g., visual impairment and neurodevelopmental disorders) ( Brown et al., 2021 ; Hou et al., 2023 ). For instance, a cross-sectional study indicated that meeting any combination of 24-HMB guidelines was linked to a lower risk of internalizing behaviors among 11,875 youths.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Meeting 24-HMB guidelines with both categorical (SL + ST and PA + ST + SL)and continuous metrics were beneficially linked to reduced depression and anxiety of those prescribed eyeglasses/contact lenses. Such findings are supported by previous studies on different age groups (e.g., preschoolers, youths, and college students, workers) ( Kitano et al., 2020 ; Ohta et al., 2023 ; Sampasa-Kanyinga et al., 2021 ; Zhu et al., 2023 ) with different health status (e.g., visual impairment and neurodevelopmental disorders) ( Brown et al., 2021 ; Hou et al., 2023 ). For instance, a cross-sectional study indicated that meeting any combination of 24-HMB guidelines was linked to a lower risk of internalizing behaviors among 11,875 youths.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have examined associations of meeting 24-HMB guidelines with some aspects of internationalizing and/or externalizing problems among different age groups (e.g., preschoolers, youths, and emerging college students) with healthy or clinical condition ( Bu et al., 2021 ; Hou et al., 2023 ; Ohta et al., 2023 ; Patte et al., 2020 ; Sampasa-Kanyinga et al., 2021 ; Zhu et al., 2023 ). For instance, a cross-sectional study indicated that meeting all three components of 24-HMB guidelines was linked to fewer internalizing and externalizing problems among preschoolers aged 3–6 years ( Zhu et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%